Heart failure and its complications in patients with diabetes: Mounting evidence for a growing burden. (December 2019) - Ferrini, Marc; Johansson, Isabelle; Aboyans, Victor
Heart failure (HF) is one of the major challenges in the management of diabetes patients. Among subjects with diabetes, up to 20% could have HF. Conversely, diabetes prevalence in HF patients varies greatly from more than 10% up to 50%. When it is present, the risk of mortality and rehospitalization increases substantially. In addition, current evidence points to an increased risk of atrial fibrillation and sudden cardiac death in patients with diabetes. The inter-relation between diabetes cardiomyopathy, left ventricular hypertrophy, coronary artery disease and renal dysfunction indicates complex and intricate pathways. Despite the great value of clinical assessment and echocardiography, there is insufficient data to suggest systematic screening for HF in asymptomatic patients with diabetes. There is little evidence to indicate that improved glycaemic control improves HF outcome in this population. In the case of established HF, the general guidelines apply in diabetes patients. However, recent advances concerning glucose-lowering treatment in patients with cardiovascular disease suggest that the choice of glucose-lowering agent is of crucial interest and should be based on the patient's phenotype. New drug classes, such as SGLT2 inhibitors, seem to be of particular benefit in these patients. In the future, new personalized strategies should aim at not only good control of the glycaemic level but also the reduction and possibly the prevention of HF onset.